2014
DOI: 10.1063/1.4900787
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis during field emission from chemical vapor deposition synthesized carbon nanotube fibers

Abstract: Hysteresis in the field emission (FE) data of a chemical vapor synthesized carbon nanotube fiber cathode is analyzed in the regime where self-heating effects are negligible. In both the forward and reverse applied field sweeps, various FE modes of operation are identified: including Fowler-Nordheim (FN) tunneling and space-charge limited emission from the fiber tip and FN emission from the fiber sidewall. Hysteresis in the FE data is linked to the difference in the field enhancement factors in the different FE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 29 publications
(34 reference statements)
2
39
0
Order By: Relevance
“…Such an effect is also observed in other carbon-derived polycrystalline materials with mixed sp 2 /sp 3 hybridization 6-10 and has been speculated to be due to different phenomena, including: electron tunneling through multiple barriers, 6 an intermediate state between the field emission and thermionic emission regimes, 7,8 or due to the space-charge effect. 7,10 Moreover, the observed saturation effect is a long-known characteristic feature of conventional semiconductors [11][12][13] which has been explored theoretically. 12,14,15 a) E-mail address: chubenko@gwu.edu…”
Section: Introductionmentioning
confidence: 99%
“…Such an effect is also observed in other carbon-derived polycrystalline materials with mixed sp 2 /sp 3 hybridization 6-10 and has been speculated to be due to different phenomena, including: electron tunneling through multiple barriers, 6 an intermediate state between the field emission and thermionic emission regimes, 7,8 or due to the space-charge effect. 7,10 Moreover, the observed saturation effect is a long-known characteristic feature of conventional semiconductors [11][12][13] which has been explored theoretically. 12,14,15 a) E-mail address: chubenko@gwu.edu…”
Section: Introductionmentioning
confidence: 99%
“…12 If outgassing is present to change the surface chemistry of the emitter, due to either desorption of the gas adsorbates, or the back bombardment from the ionized desorbed species, the FN data typically manifests hysteresis behavior. 12,13 However, it is found that the I-V curves are symmetric when sweeping the voltage up and down (not shown) for the d = 1.75 mm case. Therefore, the slope drop in the FN plots of the present FE data is most likely due to the electrical contact resistance between the CNT fiber and the substrate.…”
Section: -5mentioning
confidence: 98%
“…Note that the slope drop in the high voltage regime in the FN plot is usually attributed to space charge effects, 13,40,41 or outgassing of the field emitter. 12 When the classical Child-Langmuir law…”
Section: -5mentioning
confidence: 99%
See 2 more Smart Citations